ESTIMATIVAS DO ARMAZENAMENTO DE CARBONO NO SOLO EM ÁREAS DE AGROPECUÁRIA NOS BIOMAS AMAZÔNIA E CERRADO NO ESTADO DO MARANHÃO, BRASIL - FERREIRA, Lana Costa (2024)
The conversion of native vegetation to agricultural systems poses a potential threat to biodiversity conservation and plays a significant role in carbon sequestration and/or the emission of greenhouse gases into the atmosphere, with the sector accounting for 24% of global emissions. In light of this, the objective of this research was to analyze the impacts of converting native vegetation to agricultural systems (pastures and no-till farming) on the rates of change in soil organic carbon (SOC) stocks and biodiversity in the Amazon-Cerrado forest transition zone in the state of Maranhão, Brazil. The study was conducted across different land use types, including native vegetation, pastures, and no-till farming, allowing for a comprehensive comparison among various agroecosystems. Soil sampling materials collected from areas of native vegetation in the state of Maranhão in 2021 were used to estimate SOC stocks and change rates according to IPCC methodology. The analyses were performed using descriptive statistical methods, and maps were created to evaluate the evolution of pastures and the dynamics of native vegetation. Additionally, a literature review was conducted, and empirical models were applied to determine response variables for SOC stocks in agricultural areas. The results indicate that, considering the state of Maranhão, the conversion of native vegetation to pasture systems alters SOC stocks in the 0-30 cm depth layer after 20 years, with a decrease in SOC in degraded pasture areas (6 to 10.8%) and significant gains in well-maintained pastures (11%). Conversely, average SOC stocks showed a reduction of 7% after the conversion of native vegetation to no-till farming. However, literature review data show that the rate of SOC sequestration in no-till areas that replaced conventional tillage is 0.60 Mg C ha-1 year-1, or 9% of SOC. In this context, the information generated by this study is critical for promoting the sustainable development of agriculture in the Amazon-Cerrado transition zone in Maranhão. The analysis of the impacts of land use and management changes on soil carbon stocks not only contributes to mitigating greenhouse gas emissions but also aids in formulating strategies that integrate biodiversity conservation with sustainable agricultural production.